Sales Force Automation dalam Peningkatan Pelayanan Terhadap Pelanggan - San Karya; Joni Suhartono; Sevenpri Candra (ULTIMA InfoSys, 2017)
The purpose of this research is to analyze the company's business processes in managing customers, and design e-crm system in the field of Sales Force Automation. The method used in this research is to study literature to see SFA models to be applied, the collection of data by conducting surveys, interviews with the company as well as designing the SFA system that includes the necessary features, system design, class diagrams, sequence diagrams and screen design. The analysis of the system running can be identified problems in PT. LKI is lack of features that facilitate the company's internal applications as well as with clients in the execution of projects and no lesson learned or report that contains the project sales and employee performance. Based on the results of the research it can be concluded that PT. LKI Is required the application of Sales Force Automation that helps clients get information about the project that is being worked on, facilitates communication between internal and with clients and have a report of corporate performance as well as employees in order to achieve and enhance the company strategy in order to provide the best service for clients. Index Terms— e-CRM, Sales Force Automation